Morphological variability of stomatocyst 131 Pang & Wang (Chrysophyceae) from a freshwater shallow lake in South Urals, Russia - Ignatenko, Marina; Yatsenko-Stepanova, Tatyana; Kapustin, Dmitry (Phytotaxa, 2022)
Stomatocyst 131 Pang & Wang was described from the sedge mires and puddles in the Aershan Geological Park, China and it has not been reported from other localities since its description. We recorded stomatocyst 131 from a shallow lake Zhurmankol in South Urals, Russia. Morphological variability of this morphotype was studied using scanning electron microscopy. We showed that the width of hexagonal pattern as well as the height of the mesh edges significantly varied depending on the maturation stage of the stomatocyst. An amended diagnosis of this stomatocyst is provided.